Administrative Empowerment Policies and Their Implementation Procedures Among School Principals In Dhofar Governorate Sultanate of Oman: سياسات التمكين الإداري وإجراءات تطبيقها لدى مديري مدارس محافظة ظفار بسلطنة عمان - Mathila Salim Mohammed Mugaddam Al Mahri; Issa Khan; Mohd Abd Wahab Fatoni Mohd Balwi (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2025)
This study aimed to explore the administrative empowerment policies and the procedures for their implementation among school principals in the Dhofar Governorate of the Sultanate of Oman. The study population consisted of male and female school principals in the region. A qualitative research approach was adopted, utilizing an interview tool structured around two main themes and five key questions. The findings revealed the existence of various empowerment initiatives targeting school leaders, including professional development programs focused on educational leadership, induction training for new teachers, and support for senior teachers. These programs were found to align well with the needs and aspirations of school principals. Additionally, the study identified mechanisms for monitoring and evaluating the implementation of empowerment policies within school management, such as accountability measures and the continuous improvement of educational outcomes. However, the study also highlighted several challenges. Notably, school principals were often excluded from participating in key educational decision-making processes. There was also a shortage of targeted training on empowerment policies and implementation strategies, along with insufficient incentives to encourage the adoption of empowerment practices among principals and school staff. Based on these findings, the study recommended that the Ministry of Education create a supportive organizational environment that facilitates the practical application of administrative empowerment policies. This includes reconsidering the current incentive and reward systems and developing strategic frameworks to enhance the role of school principals through modern decision-making training and implementation techniques.